Bleomycin exerts ambivalent antitumor immune effect by triggering both immunogenic cell death and proliferation of regulatory T cells. - Hélène Bugaut (Public Library of Science (PLoS), 2013)
Bleomycin (BLM) is an anticancer drug currently used for the treatment of testis cancer and Hodgkin lymphoma. This drug triggers cancer cell death via its capacity to generate radical oxygen species (ROS). However, the putative contribution of anticancer immune responses to the efficacy of BLM has not been evaluated. We make here the observation that BLM induces immunogenic cell death. In particular, BLM is able to induce ROS-mediated reticulum stress and autophagy, which result in the surface exposure of chaperones, including calreticulin and ERp57, and liberation of HMBG1 and ATP. BLM induces anti-tumor immunity which relies on calreticulin, CD8(+) T cells and interferon-γ. We also find that, in addition to its capacity to trigger immunogenic cell death, BLM induces expansion of Foxp3+ regulatory T (Treg) cells via its capacity to induce transforming growth factor beta (TGFβ) secretion by tumor cells. Accordingly, Treg cells or TGFβ depletion dramatically potentiates the antitumor effect of BLM. We conclude that BLM induces both anti-tumor CD8(+) T cell response and a counteracting Treg proliferation. In the future, TGFβ or Treg inhibition during BLM treatment could greatly enhance BLM anti-tumor efficacy.